CFD‐Modellrechnungen zum Auftreffgrad von Partikeln auf Tropfen. Issue 12 (16th October 2013) - Pieloth, Damian; Neumann, Tim; Schaldach, Gerhard; Walzel, Peter
<x xml:space="preserve">Abstract</x> For wet scrubber simulation the knowledge of collision efficiencies of particles with droplets is needed with high resolution and in a wide range of droplet Reynolds numbers. CDF simulations enabled the calculation of collision efficiencies as a function of droplet Reynolds numbers in high resolution. For every droplet Reynolds number between 0.1 and 100 the Stokes‐Number was varied via the particle diameter, whose ratio to the droplet diameter was always smaller than 0.15. The calculated collision efficiencies presented here to some extend differ distinctively from the results known from the literature.